The Metastable City and the Politics of Crystallisation: Protesting and Policing in Kampala - Joschka Philipps; Jude Kagoro (Africa Spectrum, 2016)
When protests break out in downtown Kampala they tend to transform a fluid urban environment into bounded political camps, and myriad ambiguous concerns into comparatively clear-cut political issues. This article traces this process and conceptualises Kampala’s urban politics as a politics of crystallisation: as attempts to structure highly fluid dynamics into something concrete. The article is based on ethnographic research amongst opposition activists and the police forces. Both seek to activate political boundaries and make people gravitate towards their respective side. But in line with the fluidity of urban everyday life, they also work and collaborate across these boundaries. The national regime and the opposition thus function not as permanent, stable structures, but as processes, as fields of gravity whose emergence is incited and inhibited, financed, and policed. Drawing on Gilbert Simondon’s theory of individuation and AbdouMaliq Simone’s work on urbanity, this analytical framework offers a dynamic reading of urban contentious politics in general, and a reinterpretation of the paradoxes of power in African politics in particular.